Hot cracking elimination strategies in aluminium alloys fabricated by PBF-LB/M - Del Guercio, Giuseppe (2023)
Laser Powder Bed Fusion (PBF-LB/M) has shown to be an industrially relevant manufacturing process for the production of parts characterised by unique designs and made of several engineering materials. However, high-strength aluminium (Al) alloys, one of the most attractive material classes due to their great strength-to-weight ratio, suffer from extensive hot cracking which is yet to be fully understood and overcome. The aim of the present thesis is thus to determine multiple pathways to avoid the formation of hot cracks in high-strength Al alloys processed by PBF-LB/M. The cracking behaviour of AA2024, a well-known material characterised by great mechanical and corrosion properties, was investigated as a function of various PBF-LB/M processing parameters and chemical composition. The presence of cracks was found to be largely affected by the laser scan speed, with slower regimes characterised by lower cracking intensities. Moreover, two different cracking morphologies were observed in the microstructures, suggesting that multiple cracking phenomena occurred during PBF-LB/M fabrication. It was suggested that hot cracks initiated during a single melting event with subsequent solid-state propagation resulting in the extensive presence of such features in the as-build condition. It was found that chemical composition directly affected hot crack formation, with an addition of 3 wt% of Ni to AA2024 being beneficial in limiting the formation of hot cracks and following cold propagation. The mechanism leading to the formation of hot cracks were investigated coupling experimental observations and modelling results obtained via a multi-physics simulation of a AA2024 track surface melted using various laser regimes. This allowed the reconstruction of the spatio-temporal opportunity to form hot cracks, given by the development of detrimental intergranular pressure drops. The results showed that volumes of material solidified during the inter-pulse temporal domain are associated with higher hot cracking driving forces. Moreover, pressure drops beyond the critical threshold for hot crack formation were found in the same regimes where such features were experimentally observed. A new material agnostic descriptor of hot cracking, referred to as ‘global hot crack propensity’, was then proposed to not only address the role of chemical composition on hot crack formation, but also that of processing parameters. Based on this identified crack-free regime, the build rate of AA2024 was improved by 150% without the formation of defects or loss of mechanical performance. The previous investigations conducted on the effects of both chemical composition and manufacturing regimes on hot crack formation led to the identification of an experimental/modelling methodology aiming at the design of a bespoke crack-free alloy characterised by exceptional build rates and mechanical properties. The CALPHAD (CALculation of PHAse Diagrams) approach and micro-segregation models coupled with targeted powder-free experiments to empirically validate the simulation results proved to be an effective pathway to reduce designing times and costs. With the help of a new single metric to predict the intrinsic hot crack propensity of a given material, the custom ACN001 composition was identified, gas atomised and experimentally produced via PBF-LB/M. The results showed the absence of cracks in the as-build microstructure produced in scan speed regimes paired with extreme hot crack driving forces. Moreover, the ACN001 was found to be characterised by exceptional strength due to the presence of a fine solidification structures’ network. This thesis has developed an understanding of the various phenomena affecting hot crack formation in high-strength Al-alloys manufactured by PBF-LB/M. Moreover, the developed knowledge on the hot cracking phenomenon could be applied to other rapid solidification processes, such as, Direct Energy Deposition (DED). The results illustrated in the present research work not only represent significant scientific achievements towards the understanding of the hot cracking phenomenon but provide practical pathways to increase the applications of high-strength Al-alloys in relevant industrial sectors.